Analisis Faktor-Faktor yang Mempengaruhi Kinerja Karyawan pada PT XYZ Tangerang - Rizki Amalia Putri; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The aim of this research is to determine the performance at PT XYZ which includes performance factors, obstacles and solutions in building good performance. From the results of this research, it can be seen that employee performance at PT XYZ tends to decline due to lack of enthusiasm and work motivation. However, overall work implementation continues to be carried out well in accordance with applicable regulations and SOPs. Employee performance at PT XYZ is good, especially in the human capital division. The performance of employees in the human capital division is relatively good. This can be seen from the achievements of the Human Capital team which has succeeded in increasing sales of the company's products, as well as introducing these products to the general public. The high quality of work and dedication of the Human Capital team has helped the company achieve success in this regard.